2004
DOI: 10.1002/ejic.200400292
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of the First Cyanodiselenoimidocarbonate [C2N2Se2]2− Complexes

Abstract: )(PP)] (PP = dppe, dppm, dppf) were obtained by the reaction of the appropriate metal halide containing complex with potassium cyanodiselenoimidocarbonate. The dimeric cyanodiselenoimidocarbonate complexes [M{(C 2 -N 2 Se 2 )(η 5 -C 5 Me 5 )} 2 ] (M = Rh Ir)] were synthesised from the appropriate transition metal dimer starting material. The cy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the same work it was reported that polyselenocyanogen could alternatively be prepared from selenocyanogen by heating in high boiling solvents such as xylenes and decalin. We have examined a number of selenium-containing systems [39][40][41][42][43][44] and it is reasonable to anticipate that CSe-N analogues of the C-S-N described here could exist and thus we conducted some preliminary experiments on (SeCN) x and it is appropriate to include our preliminary observations here.…”
mentioning
confidence: 92%
“…In the same work it was reported that polyselenocyanogen could alternatively be prepared from selenocyanogen by heating in high boiling solvents such as xylenes and decalin. We have examined a number of selenium-containing systems [39][40][41][42][43][44] and it is reasonable to anticipate that CSe-N analogues of the C-S-N described here could exist and thus we conducted some preliminary experiments on (SeCN) x and it is appropriate to include our preliminary observations here.…”
mentioning
confidence: 92%
“…There are quite a few reports of platinum complexes containing selenium and phosphorus ligands, cis-P 2 PtSe 2 , and their NMR properties. 40,44,[50][51][52][53][54][55][56][57][58][59] For reasons of symmetry, most isotopomers of such complexes will constitute a higher-order spin system of type ABX 60,61 or of its limiting, non-existent, AA′X case. 62,63 Exceptions are the 31 P 2 and 31 P 2 , 195 Pt isotopomers and one 31 P 2 , 13 C isotopomer containing 13 C at the central CH 2 carbon of the dppp ligand.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The magnitude of the 2 J( 77 Se, 31 P) coupling constants obtained here is in agreement with values found in the literature. 40,44,[50][51][52][53][54][55][56][57][58][59]66 For the compound that comes closest to 1 and 2, [Pt(PPh 3 ) 2 (1,2-Se 2 -1,2-C 2 B 10 H 10 ], Wrackmeyer et al reported that the values of the 2 J( 77 Se, 31 P) coupling constants for the cis and trans pathways are very similar, around 51 Hz. 50 This could actually indicate a dynamic process, converting the AA′X spin system into A 2 X, not observed for 1, 2.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…3 ) 2 ] (R 0 ¼ H or Me; M ¼ Pd or Pt) has demonstrated that activation barriers are higher for platinum than palladium for all R, R 0 and E combinations studied. 63 Mono-, bi-and tetranuclear platinum group metal complexes of cyanodiselenoimidocarbonate, [C 2 N 2 Se 2 ] 2-, and triselenocarbonate, [CSe 3 ] 2were prepared by Woollins and co-workers, 64,65 , which was formulated on the basis of UV-Vis, RR and crystallography to possess a bis(m-S 2 dÀ ) dicopper(II) core, 68 the tetranuclear niobium complex [Nb 4 SO 5 (NCS) 10 ] 6is capped by a m 4 -sulfido ligand. 69 The counterion and crystallisation solvent are the dominant factors in determining the solid-state structures of [9]aneS 3 and [18]aneS 6 complexes of platinum(II), 70 while the first mononuclear selenoaroyl complexes were prepared from molybdenum alkylidyne precursors using mesityl isoselenocyanate.…”
mentioning
confidence: 99%